Clinical efficacy on acupuncture for perennial allergic rhinitis: a study protocol for a randomized clinical trial - Yang, Jia-xin; Ming, Shu-ren; Chen, Hui; Chen, Yue-lai (Frontiers in Allergy, 2025)
BackgroundAllergic rhinitis (AR) is a prevalent allergic disorder. Acupuncture has been widely utilized to alleviate allergic symptoms, and numerous studies have investigated its therapeutic effects on AR. However, due to the challenges associated with establishing appropriate placebo controls, few studies have directly compared acupuncture with sham acupuncture for AR treatment. This trial investigates the comparative effectiveness and tolerability of acupuncture vs. placebo needling for allergic rhinitis patients.MethodsThis clinical trial features a stratified randomization scheme with 1:1 allocation, single-blind assessment, and a total sample size of 84 participants. After screening for inclusion, qualified subjects with perennial allergic rhinitis will be randomly allocated to treatment group(accepting acupuncture, n = 42) or control group (accepting sham acupuncture, n = 42). The intervention will last over a 4-week period. The main efficacy outcome is the change in main symptom severity assessed by the Visual Analogue Scale (VAS) after each week of treatment. Secondary outcomes include the Total Nasal Symptom Score (TNSS), Efficacy Index (%) after each treatment session, time to onset of effect, Rhinitis Quality of Life Questionnaire (RQLQ) scores after each week of treatment, and the additional use rate of anti-allergic medications.ConclusionThe findings of this study aims to evaluate the effectiveness and safety of acupuncture in treating perennial allergic rhinitis through comprehensive assessment of symptom relief, time-effect relationships, quality of life improvements, and reduction in anti-allergic medication use.Trial RegistrationChinese Clinical Trial Registry (ChiCTR2400086227).